S52 MiR-181 increases in the quadriceps muscle of COPD patients after an acute bout of exercise. (14th November 2013) - Donaldson, AVJ; Tanner, RJ; Davey, CA; Hopkinson, N; Man, W D-C; Kemp, PR; Polkey, MI
Abstract : Introduction: MicroRNAs (miRs) are small non-coding RNAs that regulate gene expression and have been implicated in the control of skeletal muscle phenotype. Our group has previously shown that muscle-specific miRs are altered, and correlate with physiological parameters in the quadriceps 1 and plasma 2 of COPD patients. MiRs may therefore have a mechanistic role in the development of skeletal muscle dysfunction in COPD. We hypothesised that muscle-specific miRs are involved in skeletal muscle adaptation to exercise and that changes in quadriceps miR expression after acute exercise would differ between patients and controls. Methods: 20 COPD patients and 11 controls were studied. Fasted quadriceps biopsies were taken before and one hour after an incremental, symptom limited, cycle exercise test. Muscle-specific miR-1, -499, -133, and -206 as well as miR-181, a more widely expressed miR associated with inflammatory responses, were quantified using qPCR. Paired analyses were performed using paired T-test or paired Wilcoxon. Results: See table of characteristics (Table 1 ) Muscle miR results: MiR-1, -499, -133 did not change with exercise. MiR-181 increased x1.5 in the COPD patients only one hour after exercise (p = 0.017, controls p = 0.83). There was also a trend for miR-206 to increase in the COPD group only (p = 0.07). Conclusions: Muscle-specific miRs do not change one hour after an acute bout of exercise in COPD patients or controls. However, miR-181 increased in the quadriceps of COPD patients. MiR-181 is not restricted to, but functions in muscle, and in addition has been shown to be linked to inflammatory signalling. The difference in the response of miR-181 expression to exercise is consistent with COPD patients having a greater inflammatory response to exercise stimulus than controls. References: Lewis A, et al Thorax 2012;67:26–34 Donaldson AVJ et al Thorax 2013: EPUB 28/06/2013